2020
DOI: 10.1074/jbc.ra119.012296
|View full text |Cite
|
Sign up to set email alerts
|

12-LOX catalyzes the oxidation of 2-arachidonoyl-lysolipids in platelets generating eicosanoid-lysolipids that are attenuated by iPLA2γ knockout

Abstract: The canonical pathway of eicosanoid production in most mammalian cells is initiated by phospholipase A2-mediated release of arachidonic acid, followed by its enzymatic oxidation resulting in a vast array of eicosanoid products. However, recent work has demonstrated that the major phospholipase in mitochondria, iPLA2γ (patatin-like phospholipase domain containing 8 (PNPLA8)), possesses sn-1 specificity, with polyunsaturated fatty acids at the sn-2 position generating polyunsaturated sn-2-acyl lysophospholipids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Given that different lysoPLs are the source and that oxidized molecules are very unstable probably reduces the probability of detecting specific molecular species especially in the extracellular fluid. In support of our data Liu et al (27,28) detected eicosanoid-lysolipids formed by either COX-2 or 12-LO and iPLA 2 γ activity in murine hepatic tissue, murine and human myocardium, as well as in cells exposed to calcium ionophore. As increased concentrations of 12-HETE-LPC were detected in serum of old male mice they proposed them as specific biomarkers for various age-associated diseases (28).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Given that different lysoPLs are the source and that oxidized molecules are very unstable probably reduces the probability of detecting specific molecular species especially in the extracellular fluid. In support of our data Liu et al (27,28) detected eicosanoid-lysolipids formed by either COX-2 or 12-LO and iPLA 2 γ activity in murine hepatic tissue, murine and human myocardium, as well as in cells exposed to calcium ionophore. As increased concentrations of 12-HETE-LPC were detected in serum of old male mice they proposed them as specific biomarkers for various age-associated diseases (28).…”
Section: Discussionsupporting
confidence: 91%
“…The results underlie the differences in classical (pathogen-induced) and sterile inflammation. Eicosanoid-lysolipids, namely lysophospholipids (lysoPLs) with oxidized arachidonoyl acyl chain (e.g., HpETE-LPC, HETE-LPC) were first determined by Liu et al (27,28) in mice and human tissues and their role as possible signaling molecules was purposed, but neither their receptor nor signaling pathway had been identified. Herein we found that 15-LO oxidized 2-arachidonoyl-lysoPLs are more potent agonists for TLR4/MD-2 than oxidized PLs with two acyl chains.…”
Section: Significancementioning
confidence: 99%
“…Heart failure-induced activation of iPLA 2 γ leads to mitochondrial generation of HETEs that open the mitochondrial permeability transition pore, thus further amplifying myocardial damage [ 111 ]. Phospholipids bearing sn -2 AA are cleaved by the PLA 1 activity of iPLA 2 γ to give rise to 2-arachidonoyl-lysophospholipids, which are then oxygenized directly by cyclooxygenase-2 or 12-lipoxygenase for conversion to eicosanoid-esterified lysophospholipids [ 134 , 135 ]. The generation of eicosanoid-esterified lysophospholipids is attenuated by the absence of iPLA 2 γ, underscoring an iPLA 2 γ-initiated pathway generating new classes of lipid metabolites with potential signaling functions.…”
Section: The Ipla 2 /Pnpla Familymentioning
confidence: 99%
“…The enzymatic activities of 12S-LOX are also proposed to function in the biosynthesis of hepoxilins and maresins (92,93). Recently, 12S-LOX was shown to oxygenate 2-AA-lysoPL, proposing alternate pathways for oxylipin and oxPL biosynthesis (94).…”
Section: Loxs Act On a Broad Range Of Substratesmentioning
confidence: 99%
“…Recent studies found that COX-2, 15-LOX-2, and platelet 12S-LOX can catalyze the oxygenation of 2-AA-lysoPL released by iPLA 2 g in response to calcium ionophore stimulation (88,94). These reactions generate 2-eicosanoid-lysoPLs which are proposed to be a source of free eicosanoids as well as acting as signaling mediators themselves.…”
Section: Oxygenation Of Esterified Pufa and Biosynthesis Of Oxidized mentioning
confidence: 99%